Decentralization of Political Design in China - Benney, Jonathan (Pacific affairs, 2020)
Political posters, banners, and similar objects are extremely common in China. This article uses political design from contemporary China, particularly emphasizing the government's Chinese Dream campaign, to analyze what at first appears to be a paradox. The subjects of the various campaigns and the language they use are mandated by the central government and promoted through central and local publicity departments. However, the graphic aspects of these campaigns, such as the choice of colours, images, layout, and typeface, are much less strictly controlled, and are decided by local governments or authorities. This makes political design in China decentralized. Decentralized design is inconsistent with the principles of global marketing and with the PRC's reliance on set forms of political discourse, both of which rely on the assumption that uniformity will lead to more effective communication of messages and persuasion of the public. Evidence from local design campaigns indeed shows that Chinese political posters are often designed hastily and without expertise, resulting in strange and unpersuasive images. Despite this, the article shows that decentralized design is not paradoxical. This is largely because the Chinese party-state uses propaganda as a method of "signalling" its overall power, more than as a tool of indoctrination or persuasion about particular topics. The central government's reliance on incentives and metrics to regulate local authorities means that the production of propaganda is also a way in which local governments can signal their loyalty to the Centre.